Tuberculosis care: an evaluability study - Ardigleusa Alves Coelho; Cláudia Santos Martiniano; Ewerton Willian Gomes Brito; Oswaldo Gomes Corrêa Negrão; Ricardo Alexandre Arcêncio; Severina Alice da Costa Uchôa (Universidade de São Paulo, 2014)
OBJECTIVE: to verify whether the tuberculosis control program (TCP) is evaluable and to examine the feasibility of building an evaluation model in apriority municipality for the control of tuberculosis.METHOD: this evaluability study was conducted in a municipality in northeastern Brazil. For data collection, documental analysis and interviews with key informants were performed. For indicator validation, the nominal group technique was adopted.RESULTS: the details of TCP were described, and both the logical model and the classification framework for indicators were developed and agreed up on, with the goal of characterizing the structural elements of the program, defining the structure and process indicators, and formulating the evaluation questions.CONCLUSION: TCP is evaluable. Based on logical operational analysis, it was possible to evaluate the adequacy of the program goals for the control of tuberculosis. Therefore, the performance of a summative evaluation is recommended, with a focus on the analysis of the effects of tuberculosis control interventions on decreasing morbidity and mortality.